Phylogenetic relationships and further unknown diversity of diplostomids (Diplostomida: Diplostomidae) parasitic in kingfishers. (13th January 2023) - Achatz, T.J.; Von Holten, Z.S.; Kipp, J.W.; Fecchio, A.; LaFond, L.R.; Greiman, S.E.; Martens, J.R.; Tkach, V.V.
Abstract: Kingfishers (Alcedinidae Rafinesque) are common inhabitants of wetlands and are known to be definitive hosts to a wide range of digeneans that parasitize fish as second intermediate hosts. Among these digeneans, members of the Diplostomidae Poirier, 1886 (diplostomids) are particularly common. Recent studies of diplostomids collected from kingfishers have revealed that they are probably more diverse than currently known. This particularly concerns the genera Crassiphiala Van Haitsma, 1925 and Uvulifer Yamaguti, 1934. In the present work, we studied seven diplostomid taxa from kingfishers in Brazil, the USA and the Philippines. Partial DNA sequences of the nuclear large ribosomal subunit (28S) and mitochondrial cytochrome c oxidase I ( cox 1) genes were obtained, and 28S sequences were used to study the phylogenetic interrelationships of these diplostomids. We provide the first DNA sequences from Uvulifer semicircumcisus Dubois et Rausch, 1950 and a member of Subuvulifer Dubois, 1952. Pseudocrassiphiala n. gen. is erected for a previously recognized species-level lineage of Crassiphiala and a new generic diagnosis of Crassiphiala is provided. Crassiphiala jeffreybelli n. sp., Crassiphiala wecksteini n. sp. and Pseudocrassiphiala tulipifera n. sp. are described, and a description of newly collected, high-quality specimens of Crassiphiala bulboglossa Van Haitsma, 1925 (the type-species of the genus) is provided.